Insights Into Endovascular Management of Superior Vena Cava Obstructions - Ponti, Alexandre; Saltiel, Sarah; Rotzinger, David C.; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2021)
Superior vena cava obstruction results from any limitation of blood flow through the superior vena cava. Circulation to the heart may persist through various collateral vessels whose development depends on the level of obstruction. Depending on the level and degree of occlusive disease, the severity of clinical symptoms may vary considerably, up to lethal. Etiologies have changed dramatically in recent years, mainly due to the increasing use of intravascular devices. However, guidelines for treatment are lacking, and various options are available. Endovascular therapies developed considerably in recent years may offer a rapid improvement in symptoms and proved to be safe. However, knowledge and selection of appropriate techniques are essential to venous angioplasty, involving specific tools to guarantee satisfying outcomes. This review aims to discuss the particular venous anatomy of the upper body, the physiopathology of superior vena cava obstruction, and specificities of endovascular treatment compared with other management options.